Rethinking the Dynamics of Bilateral Trade Between Pakistan and India Under Modi’s Regime: Implications for the Regional Political Economy of South Asia - Muhammad Abdul Moiz Aman (Journal of Research in Social Sciences, 2025)
This paper examines the tendency of bilateral trade between Pakistan and India during the tenure of Prime Minister Modi. Mutual relations between the two states have taken a new turn since Modi became the Prime Minister of India in 2014. In the first phase, bilateral trade relations were cordial due to surprise visits from both sides. In the second phase, the pattern of trade fluctuated with gradual increases and decreases, reflecting the dynamic geopolitical climate. Nonetheless, in the third phase, trade was suspended by Pakistan due to the revocation of Article 35-A. The reinstallation of Modi is once again a clear indication that trade talks will not be taken seriously, despite continuous efforts from the Pakistani side. Similarly, this study also sheds light on South Asia's challenges due to the weak and zilch bilateral economic relations between Pakistan and India. Against this backdrop, the central theme of the paper circles around the impacts of modi-nomics on the bilateral relations between Pakistan and India. The current study is significant for academics, politicians, policymakers, and political economists to know how the mutual hostility between Pakistan and India has reshaped the region's economic relations and has made South Asia the least-integrated region of the world.